Discourses of Endangerment : Ideology and Interest in the Defence of Languages. - Duchene, Alexandre (Advances in sociolinguistics., 2008)
Current academic discussions and public debates about language frequently focus on the importance of defending languages against various kinds of dangers. Many of these current debates attach great importance to linguistic diversity. The debates focus on defending institutionalized languages against multilingualism, or conversely defending minority languages against the incursion of larger ones, especially the spread of English. In both cases, languages are constructed as autonomous wholes, held to need defending against attack. This book challenges such a view of language, to argue that th.